Mesoscopic modelling of additively manufactured Inconel 718 - Kergaßner, Andreas; Mergheim, Julia; Steinmann, Paul (Proceedings 6th International Conference on Additive Technologies - iCAT2016, 2016)
In additive manufacturing complex parts are built from thin layers of powder material. In selective electron beam melting (SEBM), the powder is fused by the energy of an electron beam. The electron beam is guided by electromagnetic fields allowing a very fast deflection, and thus various scan strategies. By using these scan strategies, it is possible to influence the resulting mesostructure in the material, which may range from a columnar to an equiaxed grain structure. Different macroscopic mechanical properties are expected for altered grain structures. Long and oriented grains cause highly anisotropic behaviour and a uniform grain structure results in isotropic mechanical behaviour. In this contribution the macroscopic material behaviour is simulated by means of mesoscopic Finite Element simulations. A Voronoi tessellation method is used to model the grain structure of equiaxed Inconel 718. The thermo-mechanical behaviour is modelled using a thermo gradient crystal plasticity model on the mesoscale. Computational homogenization is used to identify temperature-dependent macroscopic mechanical parameters which are compared with experimental result
Keywords: Gradient crystal plasticity; Inconel 718; Columnar grains